Primary Tuberculosis of Buccal and Labial Mucosa: Literature Review and a Rare Case Report of a Public Health Menace - Shyamkumar Sriram; Shamimul Hasan; Shazina Saeed; Syed Ansar Ahmad; Swagatika Panda (Hindawi Limited, 2023)
Tuberculosis (TB) is a chronic granulomatous infectious disorder, caused by Mycobacterium tuberculosis. Despite the recent advancements in antitubercular therapy (ATT), it remains a global public health concern. TB is a leading infectious cause of global mortality, second only to coronavirus disease 2019 (COVID-19). TB of the oral cavity is an uncommon occurrence and may be classified as a primary and secondary form. The primary tubercular lesions are extremely rare, as the intact oral squamous epithelium resists the entry of tubercle bacilli. The commonest oral TB lesion is solitary ulceration with undermined edges, usually on the tongue, that does not exhibit healing with conservative therapies. Owing to the atypical presentation, the oral TB lesions often go unnoticed during clinical examination; hence, an oral physician should be familiar with the various oral manifestations of TB. A timely diagnosis coupled with interdisciplinary treatment is the key to combat disease dissemination. This manuscript aims to report a rare case of primary tuberculosis of the buccal and labial mucosa in a 43-year-old immunocompetent male patient. Buccal and labial mucosa are the infrequently affected sites for primary oral TB lesions. A detailed literature search carried out on the Google Scholar and PubMed search engines revealed only fifteen case reports and two case series of primary tuberculosis of the buccal mucosa and labial mucosa.